Influence cross membership and qualifications of the shari’ah supervisory board’s towards the shari’ah compliance related SSB information / Iwan Fakhruddin, Mohd. Abdullah Bin Jusoh and Norlia Binti Mat Noerwani. - Fakhruddin, Iwan; Jusoh, Mohd. Abdullah; Mat Noerwani, Norlia (Universiti Teknologi Mara Selangor, 2020)
The purpose of this paper to analyze the influence of Shari’ah Supervisory Board Cross Memberships and Shari’ah Supervisory Board Qualification toward Shari’ah compliance related SSB information. In addition, this paper also explains the variable firm size as a control variable. The use of control variables so that the influence of SSB on compliance does not depend on other variables. This study reviews the Shari’ah compliance related SSB information as stated in the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) standard, primarily compliance level with AAOIFI standards No 1 and No 5 related to Shari’ah Supervisory Board (SSB). This paper finds that’s the coefficient estimates variable of SSB Cross membership is positive significant at the 10% level. The coefficient estimates on SSB Qualification is negative significant at the 5% level. Furthermore, we also find that the bank size as a control variable has a significant positive effect at 1% level.